Psychometric properties of an interviewer-administered version of the Kessler Psychological Distress scale (K10) among Dutch, Moroccan and Turkish respondents - Fassaert, T.; De Wit, M.A.S.; Tuinebreijer, W.C.; Wouters, H.; Verhoeff, A.P.; Beekman, A.T.F.; Dekker, J. (International journal of methods in psychiatric research, 2009)
The Kessler Psychological Distress scale (K10) is an instrument that is widely used to screen for mental disorders, but information is lacking on its psychometric qualities in non‐Western samples. This study used a population‐based sample (N = 725) to assess the reliability and validity of the K10 across ethnic groups in an urban area. The results were generally supportive of the K10 as a reliable and valid instrument to screen for anxiety and depression in all three groups. Cronbach's alpha was high (0.93) and the results indicated the existence of a solid single factor structure. Item bias in relation to ethnic background was minor. In each group, there was good criterion validity with respect to one‐month DSM‐IV diagnosis for depressive and/or anxiety disorder. The results nevertheless highlight the importance of cross‐cultural validation, as we found different cut‐off values for ethnic subgroups to obtain optimal sensitivity and specificity for detecting depressive and/or anxiety disorders. Copyright © 2009 John Wiley & Sons, Ltd.